2014
DOI: 10.1007/s40273-014-0151-0
|View full text |Cite
|
Sign up to set email alerts
|

Using the EuroQol EQ-5D in Swiss Cancer Patients, Which Value Set Should be Applied?

Abstract: BACKGROUND:The European Quality of Life-5 Dimensions (EQ-5D) instrument combines questionnaire responses into a single utility estimate using country-specific value sets. Countries without a national value set are advised to select one based on geographic proximity. In the absence of a Swiss value set, we used foreign value sets to gain insights into their appropriateness for use with Swiss cancer patients. METHODS: EQ-5D health states and visual analogue scale (VAS) ratings were collected in one German and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 22 publications
(23 reference statements)
0
26
0
Order By: Relevance
“…The values available to us were based on the UK value set. There is no Swiss-specific value set, but a recent study reported that the UK value set generates lower utilities than the German or French value set [ 65 ]. Because of the small difference, we have no reason to assume that this had a substantial impact on our results, at least not in the sense of favouring sofosbuvir.…”
Section: Discussionmentioning
confidence: 99%
“…The values available to us were based on the UK value set. There is no Swiss-specific value set, but a recent study reported that the UK value set generates lower utilities than the German or French value set [ 65 ]. Because of the small difference, we have no reason to assume that this had a substantial impact on our results, at least not in the sense of favouring sofosbuvir.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, more emphasis should be placed on generating locally-relevant data in the future. [199][200][201][202][203][204].…”
Section: Decision-makers' Guidance On the Approach For Estimating Utimentioning
confidence: 99%
“…The EQ-5D is one of the most feasible tools to assess individuals' QoL, and evaluates their physical, mental and social performance [12]. It has been validated and used in many studies to determine QoL in chronic diseases such as diabetes, chronic lung diseases, stroke and chronic mental illnesses [13][14][15][16][17]. Currently three versions of EQ-5D are available including EQ-5D-3 L, EQ-5D-5 L and EQ-5D-y.…”
Section: Introductionmentioning
confidence: 99%